Stakeholder engagement and decarbonization pathways: Meeting the challenges of the COVID-19 pandemic - Jäger, Jill; Brutschin, Elina; Pianta, Silvia; Omann, Ines; Kammerlander, Moritz; Sudharmma Vishwanathan, Saritha; Vrontisi, Zoi; MacDonald, Jennifer; van Ruijven, Bas (Frontiers in Sustainability, 2023)
Climate change is an extremely complex challenge characterized by its systemic nature and deep uncertainties. Thus, finding solutions requires a continuing and constructive dialogue between the research community and a wide range of stakeholders from governments, non-governmental organizations, civil society, international organizations, industry, businesses and financial institutions. The ENGAGE project (https://www.engage-climate.org/) is advancing knowledge co-production through an iterative process of stakeholder engagement with two main streams: (i) stakeholder co-design and assessment of global decarbonization pathways and (ii) stakeholder dialogues on national policies and pathways. Both the global and national stakeholder processes are designed to inform multiple project activities, including: conceptualization of feasibility and assessing the feasibility of decarbonization policies and strategies; decarbonization pathway development using integrated assessment models and considering both feasibility and equity; and assessment of the relative importance of climate change impacts vis-à-vis potential co-benefits. With the start of the COVID-19 pandemic six months after the beginning of the project, all of the stakeholder engagement activities had to be organized as online events. Between March 2020 and April 2022, 5 online workshops were organized, two at the global level and 3 at the regional/national level. This paper documents how the challenges of effectively engaging stakeholders in a co-design and dialogue process in an online setting have been met through a process of evaluation and learning that led to the introduction of new approaches and tools to support an inclusive exploration and development of low-carbon transition pathways. We show that a combination of interactive visualizations, open channel surveys and moderated breakout groups are particularly useful tools for online stakeholder engagement. The learning that has taken place through the use of these tools is demonstrated with reference to both the research team (e.g., learning about stakeholders’ views on the feasibility of decarbonization pathways) and the stakeholders (e.g. learning about experiences in other countries in dealing with the challenges of decarbonization). Despite several advantages of online engagement, such as the expanded geographical coverage and reduced CO2 emissions, the need to keep online meetings short means that important elements of face-to-face meetings cannot be included.